2023
DOI: 10.12998/wjcc.v11.i29.6984
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholangitis: Does malignant biliary obstruction vs choledocholithiasis etiology change the clinical presentation and outcomes?

Yung-Kuan Tsou,
Yi-Tse Su,
Cheng-Hui Lin
et al.

Abstract: Time series analysis is a valuable tool in epidemiology that complements the classical epidemiological models in two different ways: Prediction and forecast. Prediction is related to explaining past and current data based on various internal and external influences that may or may not have a causative role. Forecasting is an exploration of the possible future values based on the predictive ability of the model and hypothesized future values of the external and/or internal influences. The time series analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As expected, patients with biliary obstruction of malignant origin have a significantly worse clinical course compared to those with lithiasic obstruction of the bile duct, present a higher incidence of severe acute cholangitis, greater admission to critical care units, and 30-d mortality, as recently reported by Tsou et al [ 4 ], which underscores the importance of being able to differentiate the origin of biliary obstruction during the imaging study.…”
Section: To the Editorsupporting
confidence: 74%
See 1 more Smart Citation
“…As expected, patients with biliary obstruction of malignant origin have a significantly worse clinical course compared to those with lithiasic obstruction of the bile duct, present a higher incidence of severe acute cholangitis, greater admission to critical care units, and 30-d mortality, as recently reported by Tsou et al [ 4 ], which underscores the importance of being able to differentiate the origin of biliary obstruction during the imaging study.…”
Section: To the Editorsupporting
confidence: 74%
“…In summary, when conducting radiological evaluations of patients with bile duct obstruction, comprehensive consideration should be given to various imaging findings, with a focus on analyzing important imaging information. Considering the clinical implication of these diseases, I hope the discussion on the interesting articles by Tsou et al [ 4 ]. and Aydin and Irgul[ 1 ] will promote the permanent ongoing review of the imaging features of malignant and stone-induced bile duct obstruction to further improve the early recognition and appropriate management of these patients.…”
Section: To the Editormentioning
confidence: 99%
“…Acehan et al reported that the malignant etiology was an independent risk factor for in-hospital mortality in patients with acute cholangitis [6]. Tsou et al also reported that 30-day mortality was significantly higher in the malignant biliary obstruction group than in the choledocholithiasis group (5.4% vs. 0.7%, p = 0.045) among 516 patients with acute cholangitis [18].…”
Section: Discussionmentioning
confidence: 99%
“…We were intrigued by the paper “Acute cholangitis: Does malignant biliary obstruction vs choledocholithiasis etiology change the clinical presentation and outcomes?” by Tsou et al [ 1 ]. This study primarily examined laboratory data to distinguish between malignant biliary obstruction and obstruction caused by stones and underscored it’s significance.…”
Section: To the Editormentioning
confidence: 99%